The Village Government's Efforts in Increasing Public Awareness of Making Land Rights Certificates in Saotanre Village, Central Sinjai District, Sinjai Regency - AB, Fitrawati; Mukrimah, Mukrimah; Takdir, Muhammad; Esti, Anisa (PINISI Discretion Review, 2022)
Land is a place of welfare for the community, plays a strategic role in human life. Every legal action related to land, such as making land certificates, requires agents to take care of it, such as sub-district heads, village heads, PPAT (Land Deed Officials) and BPN (National Land Agency). This study aims to determine the efforts of the Saotanre Village government in increasing public awareness of the making of land rights certificates in Saotanre Village, Central Sinjai District, Sinjai Regency. This research is a qualitative research with the type of qualitative descriptive research. Data collection techniques used are observation, interviews and documentation. The informants in this study are Head of Saotanre Village; Saotanre Village officials; Saotanre Village Community; BPN (National Land Agency). Data analysis techniques are collecting data, reducing data, presenting data, and concluding.The research results show that The Saotanre Village Government has carried out socialization or counseling to the community regarding legal awareness of land registration. The inhibiting factor for the Village Government in increasing public awareness of making land title certificates is the lack of public knowledge about the importance of land registration, and caused by the existence of administrative costs that are considered burdensome to the community.